The Use of Total Physical Response (TPR) as Teaching Strategy at Elementary School - Zefa Maulina Zulfa; Sugeng Purwanto; Agnes Widyaningrum (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
AbstractLearning English using vocabulary is very useful for students at SDN 3 Bandengan, especially in the teaching and learning process in class. In teaching vocabulary, the teacher uses the Total Physical Response method so that children can understand English by playing. The purpose of this study is to analyze the teacher's method of teaching English using Total Physical Response: (1) the English teacher uses TPR to teach fourth graders at SDN 3 Bandengan, (2) the English teacher applies TPR in teaching English. The researcher used descriptive qualitative methods since the researcher completed a six-month internship at a school from August 1st, 2022 â€“ December 2nd, 2022, the data has been assessed. The researcher conducted interviews with teachers to collect information. The finding of this study is that students can understand vocabulary in English lessons using TPR.Â Keyword: teaching; vocabulary; teaching strategies; total physical response